Climate Change Significantly Alters Future Wildfire Mitigation Opportunities in Southeastern Australia. Issue 15 (31st July 2020) - Di Virgilio, Giovanni; Evans, Jason P.; Clarke, Hamish; Sharples, Jason; Hirsch, Annette L.; Hart, Melissa Anne
Abstract: Prescribed burning is used globally to mitigate the risks of wildfires, with severe wildfires increasing in frequency in recent decades. Despite their importance in wildfire management, the nature of future changes to prescribed burn windows under global warming remains uncertain. We use a regional climate projection ensemble to provide a robust spatiotemporal quantification of statistically significant future changes in prescribed burn windows for southeastern Australia. There are significant decreases during months presently used for prescribed burning, that is, in March to May in 2060–2079 versus 1990–2009 across several temperate regions. Conversely, burn windows show widespread significant increases in June to August, that is, months when burns have rarely occurred historically, and also in spring (September–October). Overall, projected changes in temperature and fuel moisture show the most widespread and largest decreases (or increases) in the number of days within their respective ranges suitable for conducting burns. These results support wildfire risk mitigation planning. Plain Language Summary: The frequency of destructive wildfires is increasing in many fire‐prone regions, threatening lives, property, and damaging the environment. To reduce the risk of wildfires occurring, agencies conduct planned, controlled, and preemptive burns of vegetation to reduce the available fuel load. Currently, in southeastern Australia, these "prescribed burns" are conducted during autumn (March–May) and early spring (September) but rarely during winter (June–August). Given climate change, we need to understand how opportunities for conducting these burns might change in future. This is particularly important for forest and woodland areas adjacent to populated urban areas. We use regional climate projection data to assess future changes to the suitability for prescribed burning. We demonstrate that over many regions, windows are projected to decrease during months currently used for conducting burns in 2060–2079 compared to 1990–2009. In contrast, they generally increase in the winter months and further into spring (September–October). This change in seasonality means that these periods could be more suitable for conducting burns in future. Future changes in burn windows are most strongly associated with changes in temperature and vegetation moisture content, though there are many other contributing factors to these changes. These findings are relevant to strategic wildfire prevention and regional risk mitigation. Key Points: Significant decreases in wildfire mitigation windows occur in March–May in 2060–2079 versus 1990–2009 but increase in June–August in 2060–2079 Projected temperature and fuel moisture changes have the largest contribution to the change in the wildfire mitigation window Locations in southeast Australia where changes in wildfire mitigation windows are projected to occur are identified on a monthly basis